化简 (x的平方y的三次方-2x的三次方y的平方)除以(-2分之1xy的平方)-{2(x-y)}的平方

2025-03-27 23:28:12
推荐回答(2个)
回答1:

(x的平方y的三次方-2x的三次方y的平方)除以(-2分之1xy的平方)-{2(x-y)}的平方

=x²y²(y-2x)/(-1/2xy²)-4(x-y)²
=-2x(y-2x)-4x²+8xy-4y²
=-2xy+4x²-4x²+8xy-4y²
=6xy-4y²

回答2:

(x^2y^3-2x^3y^2)÷(- ½ xy^2)- [2(x-y)]^2
=(x*x*y*y*y-2x*2x*2x*y*y)÷(- ½ xy*- ½ xy) – [2x-2y]*[2x-2y]
=[y*y*(y*x*x)-y*y*(2*2*2*x*x*x)]÷(¼ xy *xy) – (2x-2y)*(2x-2y)
=[y*x*x-8*x*x*x]*4xy÷xy-(2x-2y)*(2x-2y)
=[y-8x]*4-(2x-2y)*(2x-2y)
=4y-32x-(4x*x-4x*y)-(4x*y-4y*y)
=4y-32x-4x*x+4x*y-4x*y+4y*y
=y-8x-xx+xy-xy+yy
=y-8x-xx+yy
=y^3-8x